BixY1−xVO4 solid solution with porous surface synthesized by molten salt method for photocatalytic water splitting. (9th March 2017) - Yu, Lei; Fang, Wenjian; Liu, Junying; Qin, Zhen; Jiang, Zhi; Shangguan, Wenfeng
Abstract: Bix Y1−x VO4 crystallite (BYV) was successfully synthesized by molten salt method in a relatively low temperature. In this paper, the influence of calcination temperature and the weight ratio of the precursor to the salt on photocatalytic activity for water splitting were investigated. The content of Y species increases with the temperature increased, resulting the better photocatalytic activity at high temperature. The morphology on the surface of BYV can be changed with the addition of molten salt. The porous structure on the surface occurs with the addition of molten salt from the SEM, which was caused by the evaporation of molten salt at higher temperature. Compared with solid state reaction method, BYV prepared by molten salt method showed better photocatalytic performance, which was due to the lower synthesis temperature and porous structure on the surface. And BYV via 550 °C calcination with 5:1 as weight ratio showed the highest photocatalytic activity, by which the amounts of hydrogen and oxygen produced were about 1630 μmol h −1  g −1 and 680 μmol h −1  g −1 respectively. Highlights: BYV was firstly synthesized by molten salt in a relatively low temperature. Y content has an influence of photocatalytic performance of BYV. The porous structure on the surface occurs with the addition of molten salt. The higher the temperature, the more the pore structure on the surface. BYV prepared by molten salt showed better performance than solid state reaction.